New species of New World Opilioacaridae (Acari: Parasitiformes) with the description of a new genus from the Caribbean region - Vázquez, Ma. Magdalena; Klompen, Hans (Zootaxa, 2009)
Four new species and one new subspecies of Opilioacaridae are described from Mexico, Cuba, and Panama. The classification of Opilioacaridae is updated with recognition of the genus Neocarus as separate from Opilioacarus, and by recognition of a new genus, Caribeacarus, with three species from the greater Antilles and Panama. A key to the North/ Central American and Caribbean species of Opilioacaridae is provided.